Proteomics for the Identification of Biomarkers in Testicular Cancer–Review - Milardi, Domenico; Grande, Giuseppe; Vincenzoni, Federica; Pierconti, Francesco; Pontecorvi, Alfredo (Frontiers in Endocrinology, 2019)
Testicular cancer is the most common malignancy among young men and its incidence has risen over the past two decades. Both genetic and environmental factors contribute to the development of testicular cancer. A large number of biomarkers have been proposed to discriminate the different histotypes and could represent useful novel molecular targets for anticancer strategies. However, no conclusive data have been provided, especially about the usefulness of non-invasive markers in patients with testicular cancer. Proteomics is a research area that has developed rapidly in the last decade. It studies the large-scale characterization of the full protein components of a cell, a tissue, or a biological fluid. In the last decade, clinical proteomics has developed modern technology and new bioinformatic tools useful in identifying molecular markers of pathology. The main purpose of this review is to illustrate the findings of recent investigations in the discoveries of putative prognostic and diagnostic markers of testis cancer by proteomic techniques.